Clinical consequences of resistance to ALK inhibitors in non-small cell lung cancer. (2nd April 2020) - Pinto, Joseph A; Raez, Luis E; Domingo, Gelenis
ABSTRACT: Introduction : ALK rearrangements are present in 2-7% of non-small cell lung cancer (NSCLC) cases, where the EML4-ALK fusion is the most frequent. Rearrangement of ALK with other fusion partners occurs only in ≈5% of NSCLC ALK-positive. These patients have benefited from ALK inhibitors, and currently, there are three generations of drugs as the standard of care. The first-generation ALK inhibitor crizotinib is approved in the front-line setting for the treatment of advanced NSCLC; unfortunately, these tumors may eventually develop resistance to this molecule. The Second-generation A LK inhibitors, ceritinib, alectinib, and brigatinib, are approved for patients recently diagnosed or in relapse. The third-generation inhibitor lorlatininb is approved for patients who have developed resistance to any ALK inhibitor. Areas covered : In this review, an unstructured search in Pubmed and SCOPUS was conducted. We summarized the mechanisms of resistance to ALK inhibitors and its consequences in the treatment-decision making in advanced or metastatic NSCLC after failure to a first-line ALK inhibitor. Expert opinion : Currently, there are a growing number of options of therapeutic agents against ALK+ NSCLC (approved and in development); however, adequate selection and sequencing of agents are crucial to deal with the tumor evolution.